Kronika miasta Ząbkowic Śląskich i Księstwa Ziębickiego - Pawłowski, Kamil; Nowotny, Sobiesław (2023)
THE CHRONICLE OF THE TOWN ZĄBKOWICE ŚLĄSKIE AND THE DUCHY OF ZIĘBICEThe Chronicle of the Town Ząbkowice Śląskie and the Duchy of Ziębice is a translation of the originaltext kept today in Berlin. As it has been evidenced by a source query, there is a strong possibilitythat this work was held until 1945 in the town archive, located in the town hall of Ząbkowice.The translation of the manuscript was made by the historian Sobiesław Nowotny, and the scientificelaboration of the text and its editing was prepared by Kamil Pawłowski. As a result, thereader receives the translation of over 500 pages of the text written from the 18th century to thefirst half of the 19th in the German language. The chronological range of the work involves theyears 1021-1821. The text of the chronicle in a vivid way presents not only political and economicalissues connected with the history of Ząbkowice Śląskie and the Duchy of Ziębice. It alsoprovides fully plastic descriptions of everyday life, customs and morals, issues of justice, as well asatmospheric and astronomical phenomena or natural disasters. All this material creates an usuallyvivid picture of the past, perceived by the eyes of the Ząbkowice Śląskie inhabitant, devoidof the typical office craftsmanship, which is evident within the analysis of the original text. Inother words, the authors of the chronicle concentrated primarily on social events of their reality,describing them meticulously.
Keywords: Ząbkowice Śląskie; Silesia; history; narrative sources; Ziębice; Duchy of Ziębice